Pengaruh niat berperilaku dan kecerdasan spiritual terhadap pengelolaan keuangan keluarga - Ririt Faridawati; Mellyza Silvy (STIE Perbanas Surabaya, 2017)
Family financial-management is vital for achieving a financial well-being. When a family has a barely-enough income that is managed properly and wisely, it is possible that the family can live peacefully, happily, and prosperously. Although people know the importance of family financial- management, there are still many families who haven’t applied a financial management in their families. This study aimed to examine the impact of behavioral intention and spiritual intelligence on family financial-management. The sample was taken from financial managers of families that live in Gresik, Surabaya, Sidoarjo, and Mojokerto. The sample was taken using a purposive sampling based on family income with a minimum total income Rp 4,000,000/month and snowball sampling. The data were taken by distributing the questionnaires. The results show that the behavioral intention has a positive and significant effect on family financial-management and spiritual intelligence laso has a positive impact but not significant on family financial-management.